INTEGRATED MARKETING COMMUNICATION KEDAI SODARE KOPI DALAM MENINGKATKAN BRAND AWARENESS - Aldrich Novrian; Menati Fajar Rizki (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
Brand awareness is an important aspect in a coffee business. because it can expand the level of enthusiasm of business consumers. This is like what the Sodare Kopi shop is currently doing, which is currently looking to increase brand awareness using a integrated marketing communication whose sales are declining during the pandemic. This study aims to determine the integrated marketing communications mix used by the Sodare Kopi shop to increase brand awareness. The theory used in this study is the theory of integrated marketing communications which includes advertising, sales promotion, events and experiences, public relations and publicity, direct marketing, interactive marketing, and personal selling. This research is a qualitative research. The results show that the Sodare Kopi shop uses a marketing communications mix ranging from advertising through social media, Sales promotion through different variants, events and experiences by collaborating with outsiders, public relations and publicity by disseminating information through social media, direct marketing by providing knowledge. products, personal selling through positive interactions. and interactive marketing through Instagram polls.